2015
DOI: 10.1007/s12221-015-0975-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of chemically modified celluloses as templates for obtaining of alumina materials

Abstract: The main focus of this study is to investigate the influence of functional groups of cellulose and its derivatives on properties and morphology of alumina materials obtained by template synthesis. Cyanoethyl-, amidoethyl-and carboxymethylcellulose were synthesized from bleached softwood pulp and they were used as templates for alumina materials preparation. By means of methods of scanning electron microscopy and nitrogen physical sorption it was shown that properties and type of functional groups of template c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The solution of silver nitrate (0. AlOOH NPs: Boehmite NPs were synthesized as previously described [56][57][58], where 2.2 g of Al(C 3 H 7 O) 3 were added to 50 mL of deionized water at 90 • C, and a white precipitate was formed immediately. Before ultrasound treatment, the precipitate was kept at 90 • C under vigorous stirring for 15 min to complete the production of boehmite NPs and to complete the evaporation of the isopropanol formed during hydrolysis.…”
Section: Synthesis Of Np Solmentioning
confidence: 99%
“…The solution of silver nitrate (0. AlOOH NPs: Boehmite NPs were synthesized as previously described [56][57][58], where 2.2 g of Al(C 3 H 7 O) 3 were added to 50 mL of deionized water at 90 • C, and a white precipitate was formed immediately. Before ultrasound treatment, the precipitate was kept at 90 • C under vigorous stirring for 15 min to complete the production of boehmite NPs and to complete the evaporation of the isopropanol formed during hydrolysis.…”
Section: Synthesis Of Np Solmentioning
confidence: 99%
“…α‐Alumina templated with cellulose shows the smallest surface area, which can be explained by the fact that this is a template with large filaments, resulting in larger pores. Cellulose has been used before as template for γ‐alumina, resulting in a specific surface area of 33 m 2 g −1 [24] . Using the two‐step heating method, we succeeded to synthesize α‐alumina with a similarly high specific surface area as the reported γ‐alumina, thereby overcoming the problem of severe loss of specific surface area.…”
Section: Resultsmentioning
confidence: 99%
“…Hence increasing the calcination time can, even for this relatively fine template that delivers high specific surface area α‐alumina, lead to virtually phase pure α‐alumina when using our two‐step heating method, with the highest heat treatment at 1150 °C. This effect of calcination time on phase purity is interesting, because in earlier studies a variety of templates, calcination times, and temperatures was reported (1–9 h and 1100–1300 °C, respectively) when using a single‐step heating method for templated alumina [6,20,21,24,25,33,48] . In these studies, calcination times were not investigated and it was simply assumed that there was a complete transition to α‐alumina.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellulose and cellulose derivatives aerogels have been used as templates for preparation of different metal oxide [13] and ceramics [14] particles having micro to nano-size range. Regarding the use of cellulose and cellulose derivatives for preparation of alumina, cellulose pulp from softwood, cyanoethyl-, amidoethyl- and carboxy methylcellulose were synthesized from bleached softwood pulp and used as templates for alumina materials preparation [15]. The cellulosic materials were impregnated with aluminum chloride and sintered at 600–700 °C to produce alumina particles having micrometer size.…”
Section: Introductionmentioning
confidence: 99%